Institutional Framing and Entrepreneurship Capital in Uganda - Ntayi, Joseph M.; Mutebi, Henry; Kamanyi, Susan; Byangwa, Kenneth (World Journal of Entrepreneurship, Management and Sustainable Development, 2014)
Institutions are made up of formal (e.g., rules, laws, constitutions), informal (e.g., norms of behavior, conventions, self-imposed codes of conduct) constraints and their enforcement characteristics that define the incentive structure of societies and economies (North, 1994). Institutions may structure, constrain and enable the action choices of entrepreneurs (North, 1990; Williamson, 1998; DiMagio & Powell, 1983). Entrepreneurship framing is critical in the construction of business models and images which help to shape the perspectives through which people see business opportunities and economic organizations (Hallahan, 1991, 207). Extant literature reveals that institutions are responsible for the rate and direction at which innovation (Edquist, 1997) and business startup in a country. Institutional framing can have an unintentional effect on the behaviours of entrepreneurs who create wealth for nations and influence relations
Keywords: Entrepreneurship; Capital; Uganda